Wilding performance. (1st July 2015) - Hopfinger, Sarah
These Artist Pages are a response to the question, 'how can a performance practice be ecological?' By critically reflecting on a recent performance project, Wild Life, I conceptualise a 'wilding performance practice'. I suggest an ecological ethics arises by attending to performance as an ongoing entanglement of human and non-human wills and trajectories.